Critical reflections on physical culture at the edges of empire - Cleophas, F. (SUN PReSS, 2021)
This groundbreaking anthology provides a transnational view of the use of physical culture practices - to strengthen, discipline, and reimagine the human body. Exploring theses of colonialism, gender disparities, and race relations, this international examination of bodily practices is a must read for all sport historians and those interested in physical training and its meanings. Erudite, solid, enlightening, this is a truly valuable book for our field.